1994
DOI: 10.1093/geront/34.4.548
|View full text |Cite
|
Sign up to set email alerts
|

"Coping With Frustration" Classes: Development and Preliminary Outcomes With Women Who Care for Relatives With Dementia

Abstract: We describe a novel intervention program in which wives or daughters who are caregivers are taught several specific skills to enable them to manage their frustrations more effectively. These skills include learning to relax in very stressful situations and learning to be appropriately assertive with their frail elder and with other family members. Class content and structure are presented, along with preliminary data on class efficacy that is based on an N of 48 caregivers who have currently completed this par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(32 citation statements)
references
References 0 publications
1
30
0
1
Order By: Relevance
“…Some support groups are developed specificaUy for carers of stroke patients and positive carer reactions to stroke clubs have been demonstrated (Printz-Fedderson, 1990 Although support groups and stroke clubs may be effective ui aUeviatmg the effects of strain and distress, some researchers have suggested that they may be less effective than structured group interventions or individual and family treatments that can individuaUse the treatment to the caregiver's needs (Teri, 1994;Gallagher-Thompson and DeVries, 1994).…”
Section: Emotional Interventionmentioning
confidence: 99%
“…Some support groups are developed specificaUy for carers of stroke patients and positive carer reactions to stroke clubs have been demonstrated (Printz-Fedderson, 1990 Although support groups and stroke clubs may be effective ui aUeviatmg the effects of strain and distress, some researchers have suggested that they may be less effective than structured group interventions or individual and family treatments that can individuaUse the treatment to the caregiver's needs (Teri, 1994;Gallagher-Thompson and DeVries, 1994).…”
Section: Emotional Interventionmentioning
confidence: 99%
“…One example is the anger management programme developed by Gallagher- Thompson & DeVries (1994), who trained an exclusively female group of caregivers to cope with the anger and frustration they experienced in attempting to deal with the impossible demands of caregiving and other responsibilities. Their participants were taught to use relaxation and cognitive restructuring as a solution to the lack of an adequate health-care system.…”
Section: Economic and Social Impact Of Family Caregivingmentioning
confidence: 99%
“…Affective involvement is a mea-being [71]. Other studies have shown that intensive individualized caregiver interventions not only decrease sure of each member's emotional investment in another.…”
Section: Impact Of Pituitary Disease On the Family Caregivermentioning
confidence: 99%